Gender Differences in Anxiety Among COVID-19 Inpatients Under Isolation: A Questionnaire Survey During the First and Second Waves of the COVID-19 Pandemic in Japan - Tsukamoto, Ryo; Kataoka, Yuki; Mino, Koichi; Ishibashi, Naoki; Shibata, Mariko; Matsuo, Hiroo; Fujiwara, Hironobu (Frontiers in Public Health, 2021)
This study assesses the gender differences in health and anxiety, especially pertaining to mental health problems and time-course effects. We surveyed 121 patients admitted to a hospital with a COVID-19 diagnosis between March 1 and August 31, 2020. Their mental status was evaluated on admission using the Japanese General Health Questionnaire-28 (GHQ-28) and State–Trait Anxiety Inventory – Form JYZ (STAI). The patients were divided into two groups depending on the period of prevalence, that is, the first and second waves of the pandemic in Japan (from the beginning of March to the end of May 2020, Time 1 = T1; and from the beginning of June to the end of August 2020, Time 2 = T2). A multivariate analysis of covariance revealed significant differences in gender by time interactions in the GHQ-28 subscale “Insomnia and anxiety” and STAI subscale “State–Anxiety.” Post-hoc t-tests revealed that the scores of “Insomnia and Anxiety” and “State–Anxiety” were higher in women than in men at T1. However, no difference was observed at T2. Further, “Insomnia and Anxiety” and “State–Anxiety” were significantly higher at T1 than at T2 in female patients. There was no significant difference in males. Thus, female patients were more anxious and depressed in the early phase of the pandemic, whereas male patients had difficulties in coping with anxiety. We suggest more gender-specific mental care, particularly for women at the early stages of infection, and for men, at the later stage.